Analisis January Effect: Studi Empiris pada Main Board Index (Mbx) di Bursa Efek Indonesia - Tasman, Abel; Rasyid, Rosyeni; Timuria, Ika Putriana (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2015)
The purpose of this research is to examine the January effect at Main Board Index (MBX) which listed in Indonesian Stock Exchange. The population in this research is all of companies at Main Board Index (MBX) in periode of December 2009 to January 2014. Samples were selected by purposive sampling method, and generated 735 companies year observations. The type of data used is secondary data. Analysis Method used is a different test for non parametric data, such as Wilcoxon test. The result of research analysis showes that (1) there are significant differences return before and after January effect (2) there are significant differences abnormal return before and after January effect. It can be concluded that January effect occurred at the Main Board Index in Indonesian Stock Exchange.